High-thermal-conductivity two-component polyurethane structural adhesive and preparation method thereof
Through the design of two-component polyurethane structural glue, the use of modified polyether polyols and thermal fillers and other additives, the existing high-thermal structural glue has been solved, and the combination of thermal conductivity and high toughness is achieved by achieving a combination of thermal conductivity greater than 4W/(m·K) and high toughness, which is suitable for new energy vehicle batteries and other fields.
Patent Information
- Application Number
- CN202411916362.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing high thermal conductivity and toughness of the adhesives are insufficient in terms of construction properties and toughness, especially polyurethane adhesives with thermal conductivity of 3W/(m·K) or above, which have poor construction properties and low toughness, making it difficult to meet the high requirements for thermal conductivity and mechanical properties in new energy vehicle batteries and other fields.
A two-component polyurethane structural glue is used to mix the modified polyether polyol, thermal filler and other additives in a specific proportion to prepare components A and B with low viscosity and good operability, and mix them at a volume ratio of 1:1 at room temperature to form a high thermal conductivity and high toughness highly conductive polyurethane structural glue with excellent construction properties and high toughness.
The thermal conductivity after curing is greater than 4W/(m·K), while ensuring the interface adhesion and body strength of polyurethane, improving the toughness of polyurethane elastomers, and suitable for new energy vehicle batteries and other fields.
Smart Images

Figure BDA0005206911120000011 
Figure BDA0005206911120000021 
Figure BDA0005206911120000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyurethane structural adhesives, and in particular to a high-thermal-conductivity two-component polyurethane structural adhesive with excellent construction performance and high toughness, and a preparation method thereof. Background Art
[0002] The new energy industry has shown a booming development trend in recent years. Especially in 2024, the new energy industry has ushered in a new turning point. As a leader, new energy vehicles have continued to rise in market penetration. The hot sales of new energy vehicles have driven the growth of the entire new energy market, including the development of a series of industries such as lithium batteries, energy storage, and photovoltaics. With the innovation of various processes of power batteries, the energy density of batteries has been significantly improved. However, this also puts higher requirements on the safety of batteries. In order to achieve a longer range, improving the energy density of batteries is one of the core pursuits of power battery manufacturers. However, while improving the energy density of batteries, the heat generated by batteries during operation also increases. If the heat cannot be discharged in time, the heat of the battery will accumulate, causing the battery to overheat or even thermal runaway, and there will be certain safety hazards. At the same time, in order to prevent the influence of various external forces on battery components during driving, such as vibration and collision, the thermal conductivity and mechanical properties of the polyurethane structural adhesive used in power batteries are also increasingly required. However, existing high thermal conductivity structural adhesives, especially polyurethane adhesives with a thermal conductivity of more than 3W / (m·K), have the disadvantages of poor workability and low toughness. Based on this, it is very important to develop a high thermal conductivity polyurethane structural adhesive with excellent workability and high toughness. Summary of the invention
[0003] In view of the above-mentioned shortcomings that currently exist, the present invention provides a high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness and a preparation method thereof. The high thermal conductivity two-component polyurethane structural adhesive of the present invention has the advantages of low viscosity, good operability and a thermal conductivity coefficient greater than 4W / (m·K) after curing, which can not only ensure the interface adhesion and body strength of the polyurethane, but also make the polyurethane elastomer have better toughness and the like.
[0004] In order to achieve the above object, the present invention provides a high thermal conductivity two-component polyurethane structural adhesive with excellent construction performance and high toughness, which is prepared by mixing component A and component B in a volume ratio of 1:1, and calculated by mass fractions.
[0005] Component A:
[0006]
[0007]
[0008] Wherein, the modified polyether polyol is a benzene ring modified polyether polyol.
[0009] According to one aspect of the present invention, the functionality of the benzene ring-modified polyether polyol is 2-3 and the molecular weight is 400-600.
[0010] According to one aspect of the present invention, the thermally conductive filler is a filler modified by a modifier, and the filler is at least one of spherical aluminum oxide, spherical aluminum hydroxide, magnesium hydroxide, boron nitride, and aluminum nitride.
[0011] According to one aspect of the present invention, the modifier is at least one of silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570.
[0012] According to one aspect of the present invention, the filler includes boron nitride and / or aluminum nitride, and the boron nitride and / or aluminum nitride accounts for 10wt%-20wt%.
[0013] It should be noted that the proportion of boron nitride and / or aluminum nitride is 10wt%-20wt%, which means: when the filler only includes boron nitride (there are other fillers besides aluminum nitride, such as spherical aluminum oxide, spherical aluminum hydroxide, and at least one of magnesium hydroxide), the proportion of boron nitride is 10wt%-20wt%; when the filler only includes aluminum nitride (there are other fillers besides aluminum nitride, such as spherical aluminum oxide, spherical aluminum hydroxide, and at least one of magnesium hydroxide), the proportion of aluminum nitride is 10wt%-20wt%; when the filler includes boron nitride and aluminum nitride (there are other fillers besides aluminum nitride, such as spherical aluminum oxide, spherical aluminum hydroxide, and at least one of magnesium hydroxide), the total proportion of boron nitride and aluminum nitride is 10wt%-20wt%.
[0014] According to one aspect of the present invention, the other powders are at least one of bentonite, nano-silicon dioxide, fumed silica, nano-calcium carbonate, and nano-titanium dioxide; the chain extender is a polyol; the silane coupling agent is at least one of silane coupling agent KH540, silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the first water absorbent is a molecular sieve; the catalyst is any one of an organic tin catalyst, an organic bismuth catalyst, and a tertiary amine catalyst; the organic tin catalyst includes at least one of stannous octoate and dibutyltin dilaurate; the organic bismuth catalyst includes at least one of bismuth neodecanoate and bismuth isooctanoate; the tertiary amine catalyst includes at least one of triethylene diamine and triethanolamine; the diluent is at least one of phthalate, aliphatic dibasic acid ester, and phosphate.
[0015] According to one aspect of the present invention, the isocyanate is at least one of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), isophorone diisocyanate (IPDI), and 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
[0016] According to one aspect of the present invention, the toluene diisocyanate (TDI) is at least one of 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI).
[0017] According to one aspect of the present invention, the diphenylmethane diisocyanate (MDI) is at least one of 4,4'-diphenylmethane diisocyanate (4,4'-MDI) and 2,4'-diphenylmethane diisocyanate (2,4'-MDI).
[0018] According to one aspect of the present invention, the diphenylmethane diisocyanate (MDI) is 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
[0019] According to one aspect of the present invention, the polyester polyol is at least one of adipic acid polyester polyol, azelaic acid polyester polyol, and polycaprolactone polyol.
[0020] It should be noted that the molecular weight of the polycaprolactone polyol is 600-800, and the hydroxyl value is 180-220 mgKOH / g.
[0021] It should be noted that the molecular weight of the polyester diol is 1600-2400, and the hydroxyl value is 50-60 mgKOH / g.
[0022] According to one aspect of the present invention, the second water absorbing agent is at least one of p-toluenesulfonyl isocyanate Ti, methyltrimethoxysilane, and oxazolidine latent curing agent.
[0023] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness, comprising the following steps:
[0024] S1. Add modified polyether polyol, thermal conductive filler, other powders, chain extender, silane coupling agent, first water absorbent and diluent into a planetary machine, heat and dehydrate at 100-110° C. under vacuum conditions and mix and stir evenly, then cool to room temperature and add catalyst, stir and mix evenly under vacuum conditions to obtain component A;
[0025] S2. Heat the polyester polyol to 100-110° C. and dehydrate for 1-3 hours; cool to below 60° C., add isocyanate, heat to 60-80° C., stir for 2-3 hours under nitrogen protection to react, and obtain isocyanate-terminated polyurethane prepolymer; then add thermal conductive filler, other powders, a second water absorbent and a silane coupling agent, mix and stir evenly under vacuum conditions, and obtain component B;
[0026] S3, component A and component B are uniformly mixed in a volume ratio of 1:1 to obtain a high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness.
[0027] Furthermore, the preparation method of the thermal conductive filler is as follows:
[0028] Fillers with particle sizes of 1 μm, 10 μm and 70 μm are mixed in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:(95-105), and stirred at 1000-2000 r / min for 2 hours in a high-speed stirrer to obtain a thermally conductive filler; wherein,
[0029] In a specific embodiment, the filler is spherical aluminum oxide and aluminum nitride, with a mass ratio of 7.5:1.
[0030] In a specific embodiment, the filler is spherical alumina and boron nitride with a mass ratio of 7.5:1.
[0031] In a specific embodiment, the filler is spherical aluminum oxide, spherical aluminum hydroxide and aluminum nitride, and the mass ratio is 6.5:1:1.
[0032] Beneficial effects of the present invention:
[0033] (1) The present invention obtains a thermally conductive filler by adding high thermally conductive powder aluminum nitride and / or boron nitride to the filler and modifying the filler to achieve low viscosity, good operability, and a thermal conductivity greater than 4 W / (m·K) after curing;
[0034] (2) The present invention uses polycaprolactone polyol and isocyanate for prepolymerization, introduces soft segments into the polyurethane system, and the presence of benzene ring-modified polyether polyol not only ensures the polyurethane interface adhesion and bulk strength, but also makes the polyurethane elastomer have better toughness. DETAILED DESCRIPTION
[0035] To make the present invention easier to understand, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise defined, the professional terms used below are consistent with the meanings understood by professional and technical personnel in the field; unless otherwise specified, the raw materials and reagents involved in this article can be purchased from the market or prepared by known methods.
[0036] Example 1
[0037] Preparation of polyurethane prepolymer 1:
[0038] First, add 15 parts of polycaprolactone polyol and 50 parts of polyester diol to a three-necked flask, heat and dehydrate in an oil bath at 105°C in vacuum for 2 hours, and cool to 50°C. Then add 120 parts of diisocyanate, heat to 80°C, and react with vacuum stirring for 2 hours to obtain NCO-terminated polyurethane prepolymer 1. Among them, the polycaprolactone polyol is preferably the 3087 model polycaprolactone polyol of Fangyu Chemical Co., Ltd. The polyester diol is preferably the CMA-2066 model 1,6-hexanediol-adipic acid polyester diol of Huada Chemical. The diisocyanate is 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
[0039] Example 2
[0040] A method for preparing a high thermal conductivity two-component polyurethane structural adhesive comprises the following steps:
[0041] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol BASF Sovermol 760, 75 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0042] Component B: Weigh 12 parts of polyurethane prepolymer 1, 75.5 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0043] Among them, the modified spherical alumina / modified aluminum nitride is prepared by mixing spherical alumina / aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours.
[0044] Example 3
[0045] A method for preparing a high thermal conductivity two-component polyurethane structural adhesive comprises the following steps:
[0046] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol Lt-618 from Liteng Company, 75 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir under vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir under vacuum for 20 minutes.
[0047] Component B: Weigh 12 parts of polyurethane prepolymer 1, 75.5 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0048] Among them, the modified spherical alumina / modified aluminum nitride is prepared by mixing spherical alumina / aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours.
[0049] Example 4
[0050] A method for preparing a high thermal conductivity two-component polyurethane structural adhesive comprises the following steps:
[0051] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-EP280, 4 parts of modified castor oil polyol BASF Sovermol 760, 75 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0052] Component B: Weigh 12 parts of polyurethane prepolymer 1, 75.5 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0053] Among them, the modified spherical alumina / modified aluminum nitride is prepared by mixing spherical alumina / aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours.
[0054] Example 5
[0055] A method for preparing a high thermal conductivity two-component polyurethane structural adhesive comprises the following steps:
[0056] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol BASF Sovermol 760, 65 parts of modified spherical alumina, 10 parts of modified spherical aluminum hydroxide, 10 parts of modified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0057] Component B: Weigh 12 parts of polyurethane prepolymer 1, 65.5 parts of modified spherical alumina, 10 parts of modified spherical aluminum hydroxide, 10 parts of modified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0058] Among them, the modified spherical alumina / modified spherical aluminum hydroxide / modified aluminum nitride is prepared by mixing spherical alumina / modified spherical aluminum hydroxide / aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours to obtain.
[0059] Example 6
[0060] A method for preparing a high thermal conductivity two-component polyurethane structural adhesive comprises the following steps:
[0061] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol BASF Sovermol 760, 75 parts of modified spherical alumina, 10 parts of modified boron nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir under vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir under vacuum for 20 minutes.
[0062] Component B: Weigh 12 parts of polyurethane prepolymer 1, 75.5 parts of modified spherical alumina, 10 parts of modified boron nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0063] Among them, the modified spherical alumina / modified boron nitride is prepared by mixing modified spherical alumina / modified boron nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours to obtain.
[0064] Comparative Example 1
[0065] Preparation of polyurethane prepolymer 2:
[0066] First, add 15 parts of castor oil and 50 parts of polyester diol to a three-necked flask, heat in an oil bath at 105°C for 2 hours in vacuum and dehydrate, and cool to 50°C. Then add 120 parts of diisocyanate, heat to 80°C, and react with vacuum stirring for 2 hours to obtain NCO-terminated polyurethane prepolymer 2. Among them, the polyester diol is preferably Huada Chemical CMA-2066 model 1,6-hexanediol-adipic acid polyester diol. The diisocyanate is 4,4'-diphenylmethane diisocyanate (4,4'-MDI).
[0067] Comparative Example 2
[0068] A method for preparing a two-component polyurethane adhesive comprises the following steps:
[0069] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol BASF Sovermol 760, 75 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0070] Component B: Weigh 12 parts of polyurethane prepolymer 2, 75.5 parts of modified spherical alumina, 10 parts of modified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0071] Among them, the modified spherical alumina / modified aluminum nitride is prepared by mixing spherical alumina / aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours.
[0072] Comparative Example 3
[0073] A method for preparing a two-component polyurethane adhesive comprises the following steps:
[0074] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-350, 4 parts of modified castor oil polyol Lt-618 from Liteng Company, 75 parts of unmodified spherical alumina, 10 parts of unmodified aluminum nitride, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0075] Component B: Weigh 12 parts of polyurethane prepolymer 1, 75.5 parts of unmodified spherical alumina, 10 parts of unmodified aluminum nitride, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25°C for 2 hours.
[0076] The modified spherical alumina is prepared by mixing spherical alumina with particle sizes of 1 μm, 10 μm and 70 μm at a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed at a mass ratio of 1:100 and stirred at 1500 r / min for 2 hours in a high-speed stirrer to obtain the unmodified aluminum nitride. The unmodified aluminum nitride is prepared by mixing aluminum nitride with particle sizes of 1 μm, 10 μm and 70 μm at a mass ratio of 1:2:2.
[0077] Comparative Example 4
[0078] A method for preparing a two-component polyurethane adhesive comprises the following steps:
[0079] Component A: Weigh 3 parts of modified polyether polyol Suterlin ST-EP280, 4 parts of modified castor oil polyol BASF Sovermol 760, 85 parts of modified spherical alumina, 1 part of nano titanium dioxide, 0.5 parts of fumed silica, 2 parts of nano calcium carbonate, 0.5 parts of 1,4-butanediol, 0.6 parts of silane coupling agent KH550, 1.9 parts of molecular sieves, and 1.5 parts of phthalates into a planetary machine, stir in vacuum at 100°C for 2 hours, then cool to room temperature, add 0.02 parts of dibutyltin dilaurate, and stir in vacuum for 20 minutes.
[0080] Component B: Weigh 12 parts of polyurethane prepolymer 1, 85.5 parts of modified spherical alumina, 1.5 parts of nano titanium dioxide, 0.5 parts of white carbon black, 0.2 parts of p-toluenesulfonyl isocyanate Ti, and 0.3 parts of silane coupling agent KH550 into a planetary mill and stir under vacuum at 25° C. for 2 hours.
[0081] Among them, the modified spherical alumina is prepared by mixing spherical alumina with particle sizes of 1 μm, 10 μm and 70 μm in a mass ratio of 1:2:2 to obtain an initial mixture; the modifier and the initial mixture are mixed in a mass ratio of 1:100, and stirred in a high-speed stirrer at 1500 r / min for 2 hours.
[0082] Performance testing and result analysis:
[0083] The above examples and comparative examples were tested according to the following standards:
[0084] Tensile strength and elongation at break test standard: GB / T 528
[0085] Shear strength test standard: GB / T 7124
[0086] Thermal conductivity test standard: ASTM D5470
[0087] Components A and B were packed into 400 mL double tubes in a volume ratio of 1:1. A pneumatic two-component glue gun was used. A certain air pressure was used and the glue was mixed and applied with a mixing tube at a temperature of 23°C. The two-component polyurethane structural adhesive after application was subjected to relevant performance tests. The results are shown in Table 1 below.
[0088] Table 1:
[0089]
[0090] It can be seen from Table 1 that by comparing Example 2 with Comparative Example 2, it can be seen that the introduction of polycaprolactone polyol can greatly improve the toughness of the thermally conductive adhesive; by comparing Example 3 with Comparative Example 3, it can be seen that the modified thermally conductive powder can greatly improve the workability of the thermally conductive adhesive; by comparing Example 4 with Comparative Example 4, it can be seen that the addition of aluminum nitride can further increase the upper limit of the thermal conductivity of the thermally conductive adhesive.
[0091] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness, characterized in that: It is made by mixing component A and component B in a volume ratio of 1:
1. Calculated by mass: Component A: Component B: Wherein, the modified polyether polyol is a benzene ring modified polyether polyol.
2. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The functionality of the benzene ring modified polyether polyol is 2-3 and the molecular weight is 400-600.
3. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The thermally conductive filler is a filler modified by a modifier, and the filler is at least one of spherical aluminum oxide, spherical aluminum hydroxide, magnesium hydroxide, boron nitride, and aluminum nitride.
4. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 3, characterized in that: The modifier is at least one of silane coupling agent KH550, silane coupling agent KH560 and silane coupling agent KH570.
5. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 3, characterized in that: The filler includes boron nitride and / or aluminum nitride, and the boron nitride and / or aluminum nitride accounts for 10wt%-20wt%.
6. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The other powders are at least one of bentonite, nano silicon dioxide, fumed silica, nano calcium carbonate, and nano titanium dioxide; the chain extender is a polyol; the silane coupling agent is at least one of silane coupling agent KH540, silane coupling agent KH550, silane coupling agent KH560, and silane coupling agent KH570; the first water absorbent is a molecular sieve; the catalyst is any one of an organic tin catalyst, an organic bismuth catalyst, and a tertiary amine catalyst; the organic tin catalyst includes at least one of stannous octoate and dibutyltin dilaurate; the organic bismuth catalyst includes at least one of bismuth neodecanoate and bismuth isooctanoate; the tertiary amine catalyst includes at least one of triethylene diamine and triethanolamine; the diluent is at least one of phthalate, aliphatic dibasic acid ester, and phosphate.
7. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The isocyanate is at least one of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate and 4,4'-diphenylmethane diisocyanate.
8. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The polyester polyol is at least one of adipic acid polyester polyol, azelaic acid polyester polyol and polycaprolactone polyol.
9. The high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to claim 1, characterized in that: The second water absorbing agent is at least one of p-toluenesulfonyl isocyanate Ti, methyltrimethoxysilane, and oxazolidine latent curing agent.
10. The method for preparing the high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness according to any one of claims 1 to 9, comprising the following steps: S1. Add modified polyether polyol, thermal conductive filler, other powders, chain extender, silane coupling agent, first water absorbent and diluent into a planetary machine, heat and dehydrate at 100-110° C. under vacuum conditions and mix and stir evenly, then cool to room temperature and add catalyst, stir and mix evenly under vacuum conditions to obtain component A; S2. Heat the polyester polyol to 100-110° C. and dehydrate for 1-3 hours; cool to below 60° C., add isocyanate, heat to 60-80° C., stir for 2-3 hours under nitrogen protection to react, and obtain isocyanate-terminated polyurethane prepolymer; then add thermal conductive filler, other powders, a second water absorbent and a silane coupling agent, mix and stir evenly under vacuum conditions, and obtain component B; S3, component A and component B are uniformly mixed in a volume ratio of 1:1 to obtain a high thermal conductivity two-component polyurethane structural adhesive with excellent workability and high toughness.
Citation Information
Patent Citations
High-thermal-conductivity polyurethane, and preparation method and application thereof
CN115572363A